Sonography with vertical orientation feature predicts worse disease outcome in triple negative breast cancer - Wang, Haoyu (Breast, 2019)
OBJECTIVES: Triple negative breast cancer (TNBC) is a heterogenous disease and associated with unfavorable outcomes. The role of sonographic features and its association with disease outcome in TNBC is uncertain. Our study aimed to determine the prognosis predictive value of sonographic features in TNBC. METHODS: Women with TNBC patients treated between January 2009 and December 2015 were retrospectively included. Patients’ clinic-pathological, sonographic features, recurrence-free survival (RFS), and breast cancer-specific survival (BCSS) events were reviewed and analyzed. Kaplan–Meier analysis and multivariable Cox regression were used to determine the prognostic factors in TNBC. RESULTS: A total of 433 TNBC patients were included. With a median follow-up of 4.8 years, 58 (13.4%) RFS and 35(8.1%) BCSS events were detected. Besides lymphatic vascular invasion (LVI), nuclear grade III, tumor >2.0 cm, and positive axillary lymph node (ALN), multivariable analysis found that vertical orientation in ultrasound imaging was independently associated with worse RFS (Hazard Ratio (HR) = 3.238; 95% Confidential Interval (CI), 1.661–6.312; P = 0.001) and BCSS (HR = 7.028; 95% CI, 3.199–15.436; P < 0.001). TNBC with vertical orientation in ultrasound imaging had higher ALN metastasis burden than those with sonographic parallel features (2.7 ± 1.0 vs 1.5 ± 0.2, P = 0.003). CONCLUSIONS: TNBC presenting with vertical orientation in ultrasound imaging was associated with worse disease outcome and a greater number of ALN metastasis.